Mia Couto's The little word's kiss: a bridge between literature and bioethics - Combinato, Denise Stefanoni [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2016)
This paper's goal is to articulate Bioethics and Literature through a bioethical analysis of Mia Couto's tale The little word's kiss (free translation of the original title O beijo da palavrinha), seeking to promote a reflection about death and end of life care. The analysis is based on Historical-cultural Psychology theory and two bioethical referentials: vulnerability and solidarity. Like the tale, which presents the possibility of knowing and feeling the sea while it is absent, the expectancy of this text is to encourage the seek for knowledge, the elaboration of feelings and the human development through Literature.
Keywords: Bioethics; Literature; death; human development